JKN SYSTEM DEVELOPMENT STRATEGY AS A SOLUTION TO BPJS KESEHATAN DEFICIT (Jurnal Abdimas Administrasi Kesehatan, 2022)
Departing from the budget deficit of BPJS Kesehatan which has continued to occur since its implementation in January, 24-25 2022 continues to experience an overall budget overrun. Several hospitals in Indonesia are also feeling the impact of the budget deficit. Therefore researchers conducted this study to find out how it impacts. This aims to knowledge for participant to the impact of BPJS Kesehatan's budget deficit on health services. The steps taken in serving patients, both patients who are BPJS Kesehatan participants or general patients who continue to serve patients despite the budget deficit of BPJS Kesehatan are very good and noble steps. The Government through BPJS Kesehatan should do other ways to overcome the problem of BPJS Kesehatan's budget deficit so as not to burden hospitals. And, payments for hospital claims are adjusted to mandatory payments each month.